2018
DOI: 10.1155/2018/4528184
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotective Roles of a Novel Compound, MHY‐1684, against Hyperglycemia‐Induced Oxidative Stress and Mitochondrial Dysfunction in Human Cardiac Progenitor Cells

Abstract: Diabetic cardiomyopathy (DCM) is tightly linked to heart disorders and dysfunction or death of the cardiomyocytes including resident cardiac progenitor cells (CPCs) in diabetic patients. In order to restore loss of function of resident or transplanted CPCs, much research has focused on novel therapeutic strategies including the discovery of novel function-modulating factors such as reactive oxygen species (ROS) scavengers. Here, we developed and defined a novel antioxidant, MHY-1684, for enhancing the angiogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…ERK1/2 activation is associated with cell death induced by ROS [36]. However, signaling through ERK1/2 also has a prosurvival effect [55]. We demonstrated that H 2 O 2 stimulated strong phosphorylation of Akt; however, ANT pretreatment suppressed this Akt signaling in a dose-dependent manner in RDFs.…”
Section: Discussionmentioning
confidence: 69%
“…ERK1/2 activation is associated with cell death induced by ROS [36]. However, signaling through ERK1/2 also has a prosurvival effect [55]. We demonstrated that H 2 O 2 stimulated strong phosphorylation of Akt; however, ANT pretreatment suppressed this Akt signaling in a dose-dependent manner in RDFs.…”
Section: Discussionmentioning
confidence: 69%
“…However, the phosphorylation of Drp1 at Ser616 was significantly increased in acetaldehyde-treated cells. Drp1 is regulated by various posttranslational modifications, among which phosphorylation has been extensively studied [67,68]. Phosphorylation of Drp1 at Ser616 promotes both the localization of Drp1 to mitochondria and its assembly into large oligomeric structures at mitochondrial fission sites, which are important for initiating the fission event [[17], [18], [19]].…”
Section: Discussionmentioning
confidence: 99%
“…The roles of DRP1 on the induction of oxidative stress have been reported in many models: T-2 toxin treatment of human liver cells causes an increase in DRP1 expression which causes overproduction of ROS [28]. MHY-1684 activates DRP1 and inhibits mitochondrial fusion in cardiac progenitor cells, which further induces oxidative stress [29]. Prx5 inhibits ERK-Drp1-induced mitochondrial fragmentation by regulating oxidative stress [30].…”
Section: Discussionmentioning
confidence: 99%